2022
DOI: 10.1111/echo.15252
|View full text |Cite
|
Sign up to set email alerts
|

Giant coronary aneurysm in a 6‐week‐old infant, an unusual finding?

Abstract: Kawasaki disease (KD) is a self-limited vasculitis with significant morbidity and even mortality if not treated early. The diagnosis and timely treatment in children younger than 3 months is challenging as most of them have an incomplete or atypical presentation. Coronary artery abnormalities are frequent in this type of patients. We present a 6-week-old female infant with KD who developed a giant coronary aneurysm. An early diagnosis and promptly treatment, as well as the echocardiographic and multimodality f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…Numerous research studies have consistently demonstrated an increase in the incidence of KD, particularly in the atypical form (15). It can be associated with severe coronary artery complications, persistent or giant coronary aneurysms (16,17), if undisclosed timely, to which the pediatrician can ill afford to miss these diagnoses.…”
Section: Different Incidence Different Prevalencementioning
confidence: 99%
“…Numerous research studies have consistently demonstrated an increase in the incidence of KD, particularly in the atypical form (15). It can be associated with severe coronary artery complications, persistent or giant coronary aneurysms (16,17), if undisclosed timely, to which the pediatrician can ill afford to miss these diagnoses.…”
Section: Different Incidence Different Prevalencementioning
confidence: 99%